2007
DOI: 10.1111/j.1365-313x.2007.03310.x
|View full text |Cite
|
Sign up to set email alerts
|

Over‐expression of the Arabidopsis AtMYB41 gene alters cell expansion and leaf surface permeability

Abstract: SummaryThe Arabidopsis AtMYB41 gene encodes an R2R3-MYB transcription factor whose expression is not detectable under normal growth conditions in any organ or at any developmental stage analysed. It is expressed at high levels in response to drought, ABA and salt treatments, suggesting a possible role in stress responses. Transgenic lines over-expressing this transcription factor showed a pleiotropic phenotype similar to that exhibited by some mutants that affect cuticle biosynthesis. This includes a dwarf app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
168
5
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(183 citation statements)
references
References 69 publications
(183 reference statements)
9
168
5
1
Order By: Relevance
“…Many stress-responsive genes known from the literature, such as several DREB type ERF/AP2 like transcription factor genes, NCED3, ATHB-7, RD29b, a PP2C and diverse LEA genes, were strongly induced, preferentially in response to salt and osmotic stress, ABA treatment and after prolonged exposure to high temperatures (Figure 1a-c) (YamaguchiShinozaki and Shinozaki, 1994;Soderman et al, 1996;Sakuma et al, 2002;Xiong et al, 2002;Schweighofer et al, 2004;Barrero et al, 2006;Kilian et al, 2007;Cominelli et al, 2008;Hundertmark and Hincha, 2008). Seedlings transferred to cold exhibited a strong and transient induction of cold-inducible CBF transcription factor genes ( Figure 1d) (Thomashow, 1999;Chinnusamy et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Many stress-responsive genes known from the literature, such as several DREB type ERF/AP2 like transcription factor genes, NCED3, ATHB-7, RD29b, a PP2C and diverse LEA genes, were strongly induced, preferentially in response to salt and osmotic stress, ABA treatment and after prolonged exposure to high temperatures (Figure 1a-c) (YamaguchiShinozaki and Shinozaki, 1994;Soderman et al, 1996;Sakuma et al, 2002;Xiong et al, 2002;Schweighofer et al, 2004;Barrero et al, 2006;Kilian et al, 2007;Cominelli et al, 2008;Hundertmark and Hincha, 2008). Seedlings transferred to cold exhibited a strong and transient induction of cold-inducible CBF transcription factor genes ( Figure 1d) (Thomashow, 1999;Chinnusamy et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the presence of cis-ABA-responsive elements in the promoters of some wax-related genes, such as CER6 (Hooker et al, 2002), suggests that ABA directly regulates wax synthesis. Moreover, some Arabidopsis transcriptions factors that are associated with cuticle biosynthesis, such as MYB96, are known to be regulated by ABA and to be part of the ABA-mediated signaling pathway (Cominelli et al, 2008;Seo et al, 2009;Lee et al, 2015). Lastly, Cui et al (2016) showed that the expression of some cuticle related genes was affected in Arabidopsis ABA mutants, further suggesting a role for ABA in cuticle development.…”
mentioning
confidence: 94%
“…However, the expression of other regulatory factors, such as CER7, CD2, and SHINE1, was unaffected, suggesting that ABA regulates cuticle formation by influencing the expression of a subset of the transcription factors associated with cuticle formation, but not the entire regulatory network. In Arabidopsis, AtMYB41, AtMYB30, AtMYB16, AtMYB106, and AtMYB96 have been shown to regulate cuticular wax formation and, with the exception of AtMYB96, to also regulate cutin synthesis (Cominelli et al, 2008;Raffaele et al, 2008;Seo et al, 2011;Oshima et al, 2013). Since the tomato gene Solyc03g116100 was identified as the closest homolog of both AtMYB30 and AtMYB96, it may regulate both leaf cutin and wax formation; however, this remains to be tested.…”
Section: Aba Regulates Cuticle Biosynthesis During Leaf Developmentmentioning
confidence: 99%
“…While MYB96 positively regulates wax production in response to stress, MYB41 mediates the negative regulation of cutin biosynthesis in response to similar stresses. MYB41 is induced by ABA, drought, and osmotic stress, leading to the down-regulation of cutin biosynthesis genes and the disruption of cuticle structure (Cominelli et al, 2008).…”
Section: Transcription Factors and Cuticle Biosynthesismentioning
confidence: 99%